Zoomland (De Gruyter, 2024)
Despite a variety of theoretical and practical undertakings, there is no coherent understanding of the concept of scale in digital history and humanities, and its potential is largely unexplored. A clearer picture of the whole spectrum is needed, from large to small, distant to close, global to local, general to specific, macro to micro, and the in-between levels. The book addresses these issues and sketches out the territory of Zoomland, at scale. Four regions and sixteen chapters are conceptually and symbolically depicted through three perspectives: bird’s eye, overhead, and ground view. The variable-scale representation allows for exploratory paths covering areas such as: theoretical and applicative reflections on scale combining a digital dimension with research in history, media studies, cultural heritage, literature, text analysis, and map modelling; creative use of scale in new digital forms of analysis, data organisation, interfaces, and argumentative or artistic expressions. Zoomland provides a systematic discussion on the epistemological dimensions, hermeneutic methods, empirical tools, and aesthetic logic pertaining to scale and its innovative possibilities residing in humanities-based approaches and digital technologies. Enter the Zoomland game here or watch the teaser! ; Despite a variety of theoretical and practical undertakings, there is no coherent understanding of the concept of scale in digital history and humanities, and its potential is largely unexplored. A clearer picture of the whole spectrum is needed, from large to small, distant to close, global to local, general to specific, macro to micro, and the in-between levels. The book addresses these issues and sketches out the territory of Zoomland, at scale. Four regions and sixteen chapters are conceptually and symbolically depicted through three perspectives: bird’s eye, overhead, and ground view. The variable-scale representation allows for exploratory paths covering areas such as: theoretical and applicative reflections on scale combining a digital dimension with research in history, media studies, cultural heritage, literature, text analysis, and map modelling; creative use of scale in new digital forms of analysis, data organisation, interfaces, and argumentative or artistic expressions. Zoomland provides a systematic discussion on the epistemological dimensions, hermeneutic methods, empirical tools, and aesthetic logic pertaining to scale and its innovative possibilities residing in humanities-based approaches and digital technologies. Enter the Zoomland game here or watch the teaser!